PENGARUH KUALITAS LAYANAN DAN KEPERCAAN TERHADAP KEPUASAN PELANGGAN TERHADAP MITRA GRAB CABANG KOTA BENGKULU - Deky Arisca Saputra ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study was conducted to know the effect of service quality and trust on customer satisfaction toMitra Grab in Bengkulu City either partially or simultaneously. There are several factors discussed in this study, namely Service Quality (X1), and Trust (X2)on Mitra Grab in Bengkulu City (Y). The object of this research is 96 customers ofMitra Grab Bengkulu City. In this study the researcher used data collection methods by means of observation, interviews and questionnaires. With the methods using multiple linear regression analysis, it was obtained the results of the regression equation analysis: Y = 9.388 + 0.372 () + 0.301 (X2), and the results of hypothesis testing show that the quality of service resulted the value of t-count> t-table (7.756>1.98580) and (sig < = 0,000 < 0,050), and Trust shows the value of t-count> t-table (3.538>1.98580) and (sig < = 0,001 < 0,050). It can be concluded that Service Quality and Trust have a positive and significant effect oncustomer satisfaction. Keywords: Quality of Service, Trust and Customers.